Effects of adding acetic acid and molasses on fermentation quality and aerobic stability of total mixed ration silage prepared with hulless barley straw in Tibet. (4th October 2014) - Qiu, Xiaoyan; Guo, Gang; Yuan, Xianjun; Shao, Tao
Abstract In order to enlarge the feed resources in Tibet, hulless barley (Hordeum vulgare L.) straw was conserved as total mixed ration (TMR) silage by combining it with whole crop oat (Avena sativa L.), alfalfa (Medicago sativa L.) and concentrate. This experiment was carried out to study the effects of acetic acid or/and molasses on the quality of TMR silages prepared with hulless barley straw. Treatments included: control (C) silage without additive, or silage with acetic acid (A, 0.3% fresh matter basis), molasses (M, 3% fresh matter basis) and A+M. Triplicate silos were opened after 45 days of ensiling and chemical and microbial analyses were conducted on the samples. Aerobic stability was tested 2, 4 and 6 days after exposure to air. Silages of all four TMR treatments were of good quality with high lactic acid (LA) concentration and low ratios of ammonia nitrogen in total nitrogen and butyric acid contents. Both the M and A+M silages had higher concentrations of LA (P < 0.05) and lower pH (P < 0.05) than the C and A silages. During aerobic exposure, aerobic deterioration occurred in the C and M silages with air infiltration. Resistance to deterioration was sustained in the A and A+M silages, with high concentration of acetic acid and low population (~4 log cfu g−1) of yeast throughout the 6‐day test. Furthermore, the A+M treatment showed a slow change in pH and LA in comparison to the A treatment. These findings indicate that adding acetic acid inhibited the yeast growth and improved the aerobic stability. The present study suggested that A+M addition was effective for improving both the fermentation quality and the aerobic stability of TMR silages containing hulless barley straw.